Expression of protein-gene peptide (PGP) 9.5 in myocardial sleeves around the pulmonary artery and aorta in pigs - Jingping Lu, Dongsheng Zhao, Gang Zhang, Jie Gen; Qijun Shan (African Journal of Pig Farming, 2019)
A subgroup of outflow tract (OT) ventricular tachycardias (VT) originates from the aortic sinuses or the main stem of the pulmonary artery. Myocardial sleeves onto the pulmonary artery (PA) and aorta (Ao) have been recognized as a frequent site for the origin of arrhythmia. The aim of this study was to analyze PGP9.5 expression in pulmonary artery and aorta from 100 pigs hearts and relate it to the mechanism of arrhythmia. The pulmonary artery and aorta were obtained from 100 healthy pigs; longitudinal strips of tissue containing each cusp, aortic, pulmonary artery walls, left and right ventricular outflow tracts were excised and histologically analyzed. PGP9.5 was studied immunohistochemically in myocardial sleeves. Myocardial sleeves were found in 88 of 100 Aos (88%) and 20 of 100 PAs (20%). PGP9.5 positivity was observed in 89 of 90 (99%) pigs, which had myocardial sleeves. PGP9.5 immunopositivity can be detected in most pig myocardial sleeves around the PAs and Aos; this finding may contribute to the substrate for OT VTs.